1997
DOI: 10.1177/019874299702200305
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Literary Texts in Teacher Education to Promote Positive Attitudes toward Children with Emotional and Behavioral Disorders

Abstract: This study examined the effects of a literary text-based course in emotional and behavioral disorders (EBD) on changing preservice teachers' attitudes toward characteristics of children with EBD. An experimental group (N = 32) was instructed with a literary text-based approach, while a control group (N = 30) was instructed with a professional text-based approach. Both groups completed a semantic differential survey measuring attitudes toward children with EBD during the first and last weeks of the 15-week cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Furthermore, teachers often ascribe excessively negative characteristics to children with SEBD. Marlowe et al (1997) stated that these children are often described by teachers as 'aggressive', 'anxious', 'affectionless', 'unmotivated' or 'hostile'. These negative expectations often result in a sense of futility felt by both the teachers and children (Brendtro, Brokenleg, and Van Bockern 1990) and could result in behaviours and achievements consistent with those expectations (Brehm and Kassin 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, teachers often ascribe excessively negative characteristics to children with SEBD. Marlowe et al (1997) stated that these children are often described by teachers as 'aggressive', 'anxious', 'affectionless', 'unmotivated' or 'hostile'. These negative expectations often result in a sense of futility felt by both the teachers and children (Brendtro, Brokenleg, and Van Bockern 1990) and could result in behaviours and achievements consistent with those expectations (Brehm and Kassin 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Donaldson (1980) outlined six techniques that can be used to produce positive attitudinal change towards people with disabilities: (a) direct or indirect exposure to person with a disability, (b) information about the disability, (c) persuasive message, (d) addressing the dynamics of prejudice, (e) disability simulation, and (f) classroom discussion. Marlowe, et al (1997), following Donaldson's techniques, used literature-based instruction in an introduction to emotional disabilities class to address stereotypical attitudes preservice teachers held towards children with an emotional and behavioral disability. The study showed that instruction with literary texts had a more positive attitudinal change towards children with emotional and behavioral disabilities than did the group instructed with a standard textbook.…”
Section: Literature and Experiencementioning
confidence: 99%
“…Through the strong personal message conveyed in literary texts, readers are permitted to confront and accept misconceptions about persons with disabilities. The confrontation of misconceptions through literary text cans serve as a catalyst for positive attitudinal change (Marlowe, et al, 1997). …”
Section: Literature and Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…In fact, there appears to be a tendency among the research into teachers' perceptions to focus on students with a particular type of condition (Hannah and Pliner, 1983;Marlowe et al, 1997;Gilmore et al, 2003;Natof and Romanczyk, 2009;Nur and Kavakci, 2010). For instance, research into perceptions of students with social, emotional and behavioural difficulties (SEBD) (Soles et al, 2008) stressed the significance of teachers' awareness and knowledge in bs_bs_banner…”
Section: Introductionmentioning
confidence: 99%